Utilization of Mungbean’s Green House Fodder and Silage in the Ration for Lactating Dairy Cows - Rika Zahera; Idat Galih Permana; . Despal (Media Peternakan, 2015)
Green house fodder (GHF) is high quality forage that is produced by hydroponic vertical farming system in green house in short time. Silage is also high quality feed that is available all year rounds. The research aimed to evaluate productivity and nutritive value of mungbean’s GHF and its supplementation effect with and without silages based ration on dairy cow performances. The research was divided into two experiments. The first experiment studied the seed density (A1= 1.5 kg/m2; A2= 2.5 kg/m2; A3= 3.5 kg/m2) in bioslurry:ABmix 25:75 media as nutrient solution and used randomized block design. The second experiment studied mungbean’s GHF supplementation that used twelve lactating dairy cows with 2 x 2 randomized factorial block design 2 x 2. Factor 1 compared silages utilization (S0= without silages; S1= silages) and factor 2 tested mungbean’s GHF supplementation level (G0= 0% DM; G1= 5% DM). The results showed that A1 produced the highest biomass conversion (5.27). GHF had high digestibility and fermentability indicated that GHF had potential as dairy feed. Supplementation of GHF increased nutrient intake. Silage is a high quality feed, so that GHF supplementation did not give significant effects on nutrient digestibility and milk production. It can be concluded that the low seed density (1.5 kg/m2) had high productivity and nutrition quality, and its supplementation increased nutrient intake, but did not affect nutrient digestibility and milk production.Key words: green house fodder, mungbean, bioslurry, dairy cow, silages